Penanaman Nilai-Nilai Karakter sebagai Upaya Meningkatkan Etos Kerja Guru dan Karyawan Menuju Neswa Lembah Sunyi Sekolah Berkualitas - A. Marsiti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
The porpose of this best practice is to improve the work ethics of teachers and employees also the Students spirit in learning which the goal is to improve the quality of learning at SMK Negeri 1 Warureja. The formulation of the problems in this scientific work are: (1) How to improve the work ethic and work hard for teachers and employees of State Vocational School 1 Warureja ?, (2) What is the impact of discipline, and hard work on the work ethic of teachers and employees of State Vocational School 1 Warureja and (3) What are the obstacles that arise in instilling discipline, and hard work in an effort to improve the work ethic of teachers and employees of SMK Negeri 1 Warureja, and how to overcome them? The methode used were coacking, interviews, observation and the instruments used were questionnaire as well as documentation. The results achieved through fostering discipline and hard work in an effort to improve the work ethic of teachers and employees or the learning enthusiasm of students of SMK Negeri 1 Warureja, are: (1) as school residents both teachers and employees have a high work ethic (teacher questionnaire results 4.67; results Employee questionnaire 4.09, and for students having high enthusiasm for learning (student questionnaire results 4.09), (2) as a citizen of the teacher / employee school or students trying to do their duties and obligations as well as possible (results of teacher questionnaire 4.47, employee questionnaire results 4.33, student questionnaire results 4.06) (3) teachers / employees or students have high discipline (teacher questionnaire results 4.44, employee questionnaire results 4.33, student questionnaire results 4.16), and (4) as school residents both teachers / employees have hard work enthusiasm (teacher questionnaire results 4.67, employee questionnaire results 4.66,) and students have a high enthusiasm for learning (student questionnaire results 4.53). (5) Development of disciplined and work training the most effective race against teachers and employees and students is by example. The conclusion of planting the character values as an effort to improve the work ethic of teachers and employees through mechanisms: (1) Preparation, (2) Implementation, and (3) Monitoring. The results achieved through the inculcation of the value of discipline and hard work can improve the work ethic of teachers and employees of SMK Negeri 1 Warureja in the 2019-2020 Academic Year. Recommendations: (1) The Head of the Education Office of Central Java Province, can use the cultivation of discipline and hard work as an effort to improve the work ethic in the ranks of the Department of Education and other Schools, (2) The results of the implementation of the inculcation of disciplined values and hard work practically it can also be used by school principals as an effort to improve the work ethic of teachers and employees as well as efforts to improve the quality of education in general and the quality of learning of SMK Negeri 1 Warureja in particular.